Ivabradine in patients with heart failure: a systematic literature review - Zeba M. Khan; Jean Baptiste Briere; Elzbieta Olewinska; Fatma Khrouf; Mateusz Nikodem (Taylor & Francis Group, 2023)
ABSTRACTBackground: Heart failure is a chronic disease linked with significant morbidity and mortality, and uncontrolled resting heart rate is a risk factor for adverse outcomes. This systematic literature review aimed to assess the efficacy, safety, and patient-reported outcomes (PROs) of ivabradine in patients with heart failure (HF) with reduced ejection fraction (HFrEF) in randomized controlled trials (RCTs) and observational studies.Methods: We searched electronic databases from their inception to July 2021 to include studies that reported on efficacy, safety, or PROs of ivabradine in patients with HFrEF.Results: Of 1947 records screened, 51 RCTs and 6 observational studies were identified. Ivabradine on top of background therapy demonstrated a significant reduction in composite outcomes including hospitalization for HF or cardiovascular death. In addition, observational studies suggested that ivabradine was associated with a significant reduction in mortality. Across all studies, ivabradine use on top of background therapy was associated with greater reductions in heart rate, improved EF, and improved health-related quality of life (QoL) and comparable risk of total adverse events compared to those treated with background therapy alone.Conclusions: Ivabradine on top of background therapy is beneficial for heart rate, hospitalization risk for HF, mortality, EF, and patients' QoL. Moreover, these benefits were achieved with no significant increase in the overall risk of total adverse events.